Photo Editing Training for PKK Group in Rambung Barat Village Using Free Smartphone Applications as an Effort to Promote Attractive Products - Manika, Fuzy Yustika; Br Ginting, Dewi Sartika; Yuliaty, Tetty; Putri, Iftitah Maghfirah Kesuma; Fadhillah, M.Ardhi; Sembiring, Erlangga; Siregar, Wahyu Hidayat; Aldeena, M.Iqbal; Kamil, Ibnu Julianda (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Since the outbreak of COVID-19, the business income of women members of the PKK group in Rambung Barat Village has decreased because the purchasing power of the surrounding community has decreased. Marketing of business products is only done locally. These problems require a strategy so that products can be marketed widely by utilizing digital marketing. The women members of the PKK group already have solutive and innovative products but if the product photos presented are less attractive then consumers will not be interested. In online marketing, consumers only see photos of the products offered. Creating attractive product photos and being able to convey the message of the product is expensive if it has to be done by a professional. This activity aims to increase knowledge and expertise in taking product photos that are carried out independently. So that it can compete and attract potential consumers to make purchases. The method used is by conducting training and mentoring. Participants filled out the pretest and post test to see the extent of the knowledge gained. The results of the activity show that this activity has a positive impact. There is increasing knowledge about using smartphone applications to make good and attractive product photos. PKK members have been able to make product photos that can be used in digital marketing. So that later the product is increasingly known to the wider community and the existing products are increasingly sold in the market.